Cocido y crudo. - Saltz, Jerry; Villaespesa, Mar; Mosquera, Gerardo; Fisher, Jean; Cameron, Dan (Madrid : MNCARS - Museo Nacional Centro de Arte Reina Sofia, 1994)
Antoni, Janine ; Arienti, Stefano ; Benning, Sadie ; Xu Bing ; Cabrita Reis, Pedro ; Cadieux, Geneviève ; Civera, Victoria ; Dávila, Juan ; Delvoye, Wim ; Dion, Mark ; Dittborn, Eugenio ; Doherty, Willie ; Dujourie, Lili, Dumas, Marlene ; Durham, Jimmie ; Eichhorn, Maria ; Fleury, Sylvie ; Green, Renée ; Hatoum, Mona ; Hernandez-Diez, José Antonio ; Hill, Gary ; Hirst, Damien ; Jubelin, Narelle ; ECHO ; Kingelez, Bodys Isek ; Kippenberger, Martin ; etc.
Cocido y crudo, Museo Nacional Centro de Arte Reina Sofia, Madrid, 14 de diciembre de 1994 - 6 de marzo de 1995
boek